Analysis of social studies Teacher problems in developing lesson plans of Merdeka curriculum - Tanio, Gusti Indra; Ratnawati, Nurul; Wiradimadja, Agung; Wahyuningtyas, Neni (Jurnal Teori dan Praksis Pembelajaran IPS, 2024)
Implementing the Merdeka curriculum has impacted changes in several documents, including learning tools, one of which is a lesson plan. In its development, there are still many teachers who experience difficulties. This research aims to analyze the problems and causal factors experienced by social studies teachers in preparing RPP for the Merdeka curriculum for junior high schools in Batu City. The research method used in this study is qualitative descriptive, involving as many as 13 teachers, and data was obtained in the form of interviews. The research data was obtained from non-participatory observations, semi-structured interviews, and documentation. The study results show that teacher problems are found, namely the principles of preparing lesson plans, determining initial competencies, determining the profile of Pancasila students, determining learning outcomes, determining learning objectives, determining triggering questions, designing learning activities, and making learning assessments. Then, the factors that cause the problem are that teachers do not understand the changes in the Merdeka curriculum, the components of the lesson plan are different from the previous learning design, the teacher's competence in developing the lesson plan is relatively low, and the mastery of technology is lacking. The results of this study recommend that stakeholders in schools and the Batu City education office improve teachers' understanding and competence through training and workshops regarding the development of lesson plans that follow the Merdeka curriculum.